Early leaf removal as strategy to reduce Botrytis bunch rot on Chardonnay grapevine in high altitude region of Santa Catarina state - Würz, Douglas André; Fontanella Brighenti, Alberto; Silva Souza, Deivid; Reinher, Juliana; Canossa, Adrielen; Rufato, Leo (Scientia Agraria Paranaensis, 2021)
The objective of this work is to compare different periods of leaf removal in the control of this disease in Chardonnay grown in high altitude regions of Santa Catarina - Brazil. The experiments were conducted in São Joaquim city, in 2018 and 2019 growing seasons. The treatments consisted of leaf removal at the phenological stages of full bloom, buckshot berries, pea-sized berries, veraison, and the control treatment, in which the plants without leaf removal. Epidemiological variables were calculated from: beginning of symptom appearance; times to reach maximum disease incidence and severity; maximum disease incidence and severity; and areas under the incidence and severity disease progress curves. The results of the present work show the importance of early leaf removal of Chardonnay in management of Botrytis cinerea, it is recommended to be carried out at the phenological stages of full bloom, buckshot berries and pea-sized berries, as it provides a reduction in the maximum severity of B. cinerea and a reduction of AUSDPC. The rate of disease progression demonstrated that B. cinerea infection and development was faster in plants not submitted to leaf removal. the management of early leaf removal (performed before veraison) is more efficient to prevent or suppress the development of B. cinerea in Chardonnay in edaphoclimatic conditions of high altitude regions of Santa Catarina (Brazil).